Pendampingan Pembuatan Nomor Induk Berusaha (NIB) dan Branding Produk dalam Upaya Pengembangan UMKM di Dusun Sukomoro Desa Puncu Kec. Puncu Kediri - Sutantri Sutantri; Imma Rokhhmatul Aysa; Khairan Khairan (Pusat Riset dan Inovasi Nasional, 2022)
One very important aspect in the development of Micro, Small and Medium Enterprises (MSMEs) is the form of granting permits for carrying out business activities, which are given by the authorities to business actors. Legality in a business also has a very important role, because it is used as an indication that the business being established is feasible and running. NIB is a business identity number used by business actors to obtain business permits and commercial or operational permits. The community service activities carried out were creating Business Identification Numbers through Online Single Submission (OSS) and marketing to several small business partners, due to a lack of understanding of gadget applications and a lack of product marketing strategies in Sukamoro Hamlet, Puncu Village. The purpose of this service is to provide understanding to the public about the importance of having business legality and product marketing. The method used is observation. The number of umkm in Sukomoro Hamlet is 11 umkm, and 1 umkm does not yet have an NIB. The UMKM was pleased and succeeded in forming an NIB so that it was able to obtain an NIB legality certificate, namely the